Salmonella enterica serovar Typhimurium ATCC 14028S is tolerant to plant defenses triggered by the flagellin receptor FLS2 - Wahlig, Taylor A (FEMS Microbiol Lett, 2019)
Salmonellosis outbreaks associated with sprouted legumes have been a food safety concern for over two decades. Despite evidence that Salmonella enterica triggers biotic plant defense pathways, it has remained unclear how plant defenses impact Salmonella growth on sprouted legumes. We used Medicago truncatula mutants in which the gene for the flagellin receptor FLS2 was disrupted to demonstrate that plant defenses triggered by FLS2 elicitation do not impact the growth of Salmonella enterica serovar Typhimurium ATCC 14028S. As a control, we tested the growth of Salmonella enterica serovar Typhimurium LT2, which has a defect in rpoS that increases its sensitivity to reactive oxygen species. LT2 displayed enhanced growth on M. truncatula FLS2 mutants in comparison to wild-type M. truncatula. We hypothesize that these growth differences are primarily due to differences in 14028S and LT2 reactive oxygen species sensitivity. Results from this study show that FLS2-mediated plant defenses are ineffective in inhibiting growth of Salmonella entrica 14028S.